Retrograde Semaphorin-Plexin Signaling Drives Homeostatic Synaptic Plasticity - Orr, Brian O. (Nature, 2017)
Homeostatic signaling systems ensure stable, yet flexible neural activity and animal behavior(1–4). Defining the underlying molecular mechanisms of neuronal homeostatic signaling will be essential in order to establish clear connections to the causes and progression of neurological disease. Presynaptic homeostatic plasticity (PHP) is a conserved form of neuronal homeostatic signaling, observed in organisms ranging from Drosophila to human(1,5). Here, we demonstrate that Semaphorin2b (Sema2b) is target-derived signal that acts upon presynaptic PlexinB (PlexB) receptors to mediate the retrograde, homeostatic control of presynaptic neurotransmitter release at the Drosophila neuromuscular junction. Sema2b-PlexB signaling regulates the expression of PHP via the cytoplasmic protein Mical and the oxoreductase-dependent control of presynaptic actin(6,7). During neural development, Semaphorin-Plexin signaling instructs axon guidance and neuronal morphogenesis(8–10). Yet, Semaphorins and Plexins are also expressed in the adult brain(11–16). Here we demonstrate that Semaphorin-Plexin signaling controls presynaptic neurotransmitter release. We propose that Sema2b-PlexB signaling is an essential platform for the stabilization of synaptic transmission throughout life.